PERCEPTION OF PATIENTS ON ART ABOUT THE SERVICES AVAILED AT LINK ART CENTERS IN SELECTED STATES OF INDIA - Sogarwal, Ruchi; Shkula, S K; Bachani, D (Indian Journal of Community Health, 2012)
Objectives: The present study was attempted to assess the perception of patients on ART about the services availed at Link ART Centers (LAC) in selected states of India. Methods: A total of 354 PLHAs were selected from 20 systematic randomly selected LACs from Gujarat, Maharashtra, Rajasthan and Uttar Pradesh. Results: Study reveals that majority (97%) of the patients seeking services from LACs made regular visits to the center. It was found that 57 percent of the patients had spent less than 100 rupees during the last visit. More than 95 percent of the clients reported waiting time less than 30 minutes for availing counseling and collection of drugs at LACs. The mean±SD score of patient’s level of satisfaction with the services availed at LACs is 4.7±0.5. Conclusions: Study concludes that while majority of the patients were satisfied with the services at LACs, there is need of strengthening the existing ‘package’ of services in these centers and expand the network across the country.